The association between a stress-is-enhancing mindset and internet gaming disorder was mediated by behavioral disengagement among medical undergraduate students: a multi-center survey in China - Haiyan Xiang; Lijing Liu; Xin Su; Ying Yang; Haifeng Xue; Bo Liu; Yanling Tu; Ruxin Wang; Xinxin Mo; Hongye Luo; Lijuan Li; Xianzhang Tian; et al. (BMC Psychiatry)
Abstract Background The stress-is-enhancing mindset has beneficial effects on physical, psychological, and emotional well-being. However, its association with internet gaming disorder (IGD) had not been investigated. By integrating stress mindset into the cognitive evaluation process of commonly used stress coping theories, this study examined the association between stress mindset and IGD and explored relevant mediation mechanisms via behavioral disengagement. The gender differences in the above associations and mediations were also explored. Methods An online, anonymous, cross-sectional survey was conducted among medical undergraduate students from seven cities (Baotou, Qiqihar, Harbin, Wenzhou, Guangxi, Dali, and Shantou) in China from December 2023 to February 2024. The final sample size was 8,552 (a mean response rate of 71.0%). The DSM-5 IGD Checklist, the Stress Mindset Measure-General, and the behavioral disengagement subscale of Brief-Coping Orientation to Problems Experienced Inventory were used to assess IGD, stress mindset, behavioral disengagement, respectively. Multivariate logistic regression analyses were conducted to test the significance and direction of the determinants of IGD. Path analysis was performed to examine the mediation mechanisms and the moderation effect of gender. All these analyses were adjusted for background factors. Results Of all participants, the prevalence of IGD was 7.5%, and males had significantly higher prevalence than females (14.7% versus 7.4%, p < 0.001). Multivariate logistic regression analyses found that the stress-is-enhancing mindset was negatively associated with IGD (ORa = 0.94, 95% CI: 0.92 ~ 0.97) while behavioral disengagement was positively associated with IGD (ORa = 1.66, 95% CI: 1.57 ~ 1.76). Path analysis found that behavioral disengagement fully mediated the association between stress mindset and IGD, i.e., the stress-is-enhancing mindset was negatively associated with behavioral disengagement, which in turn was positively associated with IGD. However, gender did not significantly moderate the associations between stress mindset and behavioral disengagement, between behavioral disengagement and IGD, and between stress mindset and IGD. Conclusions This study observed the relatively high prevalence of IGD among Chinese medical undergraduate students. It also revealed that the stress-is-enhancing mindset was potentially protective against IGD, and behavioral disengagement might fully explain such a beneficial effect. Future longitudinal and interventional studies are needed to verify and extend these findings.